Quantitative ultra-widefield fluorescein angiography biomarkers in diabetic retinopathy and association with treatment and progression - Iyengar RS; Fleifil S; Aaberg MT; Yu G; Patel TP; Powell C; Tran AK; Paulus YM (Clinical Ophthalmology)
Rahul S Iyengar,1,2 Salma Fleifil,1 Michael T Aaberg,1,3 Gina Yu,1,4 Tapan P Patel,1,5 Corey Powell,6 Annie K Tran,1 Yannis M Paulus1,5,7 1Department of Ophthalmology and Visual Sciences, W. K. Kellogg Eye Center, University of Michigan Medical School, Ann Arbor, MI, USA; 2Department of Ophthalmology, Roski Eye Institute, Keck School of Medicine at USC, Los Angeles, CA, USA; 3Department of Medicine, Emory University School of Medicine, Atlanta, GA, USA; 4Department of Ophthalmology, Byers Eye Institute, Stanford Health Care, Palo Alto, CA, USA; 5Department of Ophthalmology, Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 6Department of Consulting for Statistics, Computing and Analytics Research, University of Michigan, Ann Arbor, MI, USA; 7Department of Biomedical Engineering, Johns Hopkins University, Baltimore, MD, USACorrespondence: Yannis M Paulus, Wilmer Eye Institute Department of Ophthalmology Johns Hopkins University, 600 N. Wolfe St, Baltimore, MD, 21287, USA, Tel +1 410 955-3518, Email ypaulus1@jh.eduPurpose: To determine if demographic factors and calculated areas of nonperfusion (NP) and neovascularization (NV) on ultra-widefield (UWF) fluorescein angiography (FA) in the eyes of patients with diabetes are associated with treatment with intravitreal injections (IVIs), panretinal photocoagulation (PRP), and diabetic retinopathy (DR) progression.Patients and Methods: This retrospective, cross-sectional study included 363 patients (651 eyes) treated at the University of Michigan Kellogg Eye Center between January 2009 and May 2018. Eligible participants were 18 years or older diagnosed with diabetes who received UWF FA. Patients with previous PRP or poor-quality images were excluded. Main outcome measures included comparison analyses of measured surface areas in millimeters squared (mm2) of total and regional retinal nonperfusion and neovascularization, number of IVIs and PRP treatments, and DR progression.Results: Our cohort received 3,041 IVIs and 878 PRP treatments with a mean follow-up of 915 days (SD ± 714). IVIs were positively associated with posterior NP (difference, 1.15 mm2; 0.43– 1.86; P= 0.0017). PRP treatments were positively associated with total NP (difference, 27.24 mm2; 14.68– 39.79; P< 0.001) and total NV (difference, 1.75 mm2; 0.84– 2.65; P< 0.001), as well as regional areas. While progression was not associated with NP/NV area, it was positively associated with a pre-existing diagnosis of type 2 as compared to type 1 diabetes (147% increase; 7– 373% increase; p=0.03).Conclusion: Areas of NP and NV on UWF FA demonstrated associations with PRP and IVIs in DR patients.Keywords: diabetic retinopathy, intravitreal injections, panretinal photocoagulation, ultra-widefield fluorescein angiography